Assessment of genetic diversity in chinese hulless barley accessions for qualitative traits (Bioscience Journal, 2021)
Cultivated barley (Hordeum vulgare L.) has been proven to be an economically important model plant and having large genetic diversity among the species. The effective exploitation of qualitative characters in barley can be measured by its genetic diversity and interrelationship. This study aims to determine the assessment of genetic diversity in Chinese hulless barley accessions for qualitative traits. Presently, in this study, the genetic diversity of 208 Chinese hulless barley from different Provinces of China, 111 genotypes were from the Tibet plateau, 30 Sichuan, 2 USA, 1 Canada, 12 Gansu, 51 Qinghai, 1 Yunnan was investigated; collected. Almost all the qualitative traits including crude protein, fiber, starch, neutral detergent fiber, and acid detergent fiber exhibited significantly high variability (p≤0.0001) among the cultivars. The data were analyzed using Statistics 8.1. In this study, significantly high variation was observed between starch content and neutral detergent fiber (23.64% and 11.54%). However, the highest diversity is based on the magnitude of the coefficient of variation exhibited in crude protein (13.82%), starch (12.87%), and fiber (12.17%). There was a significantly positive correlation between fiber, acid detergent fiber, and neutral detergent fiber except for starch content with crude protein and fiber that exhibited a significant negative correlation (r= -0.38*** and r= -0.92***). A large genetic diversity was observed through cluster analysis among all the 208 barley accessions, distance coefficient ranging between 0.28 and 75.86. The histogram revealed that frequency distributions of 208 different genotypes of hulless barley crop with all five different characters, crude protein, fiber, starch, neutral detergent fiber, and acid detergent fiber, showed normal distribution. It is concluded that this hulless barley study showed genetic diversity among the accessions and confirmed genetic diversity in various traits used.